2020
DOI: 10.1080/05704928.2020.1791152
|View full text |Cite
|
Sign up to set email alerts
|

The use of Fourier Transform Infrared (FTIR) spectroscopy in skin cancer research: a systematic review

Abstract: Skin cancers are one of the most frequently occurring diseases in humans that pose severe health issues.Fourier Transform Infrared (FTIR) spectroscopy in cancer research has gained considerable attention because of its ability to provide biochemical information in addition to being compatible with traditional histopathology. With this review, we aim to identify all skin cancer studies which have been conducted using FTIR spectroscopy and depict different methodologies that have been used to analyse FTIR spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…The last prominent band observed at 3298 cm -1 is amide A which occurs due to stretching vibration of NH groups of proteins. The prominent spectral bands are well characterized by all cell lines [8].…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The last prominent band observed at 3298 cm -1 is amide A which occurs due to stretching vibration of NH groups of proteins. The prominent spectral bands are well characterized by all cell lines [8].…”
mentioning
confidence: 94%
“…The analysis of acquired spectra can be automated using machine learning algorithms, making the classification of lesions less prone to operator errors. We have recently reviewed the efficacy of FTIR spectroscopy in skin cancer research [8]. FTIR spectroscopy has been previously shown to discriminate between healthy and diseased conditions of various skin cancers [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Tissue samples used in FTIR microspectroscopy are most often fixed with formalin and embedded in paraffin, i.e., formalin-fixed paraffin embedded (FFPE) samples. 1 Paraffin serves as a support medium during sectioning and aids in preserving the sample for future analysis. Thin sections are cut with a microtome and placed on a suitable substrate, depending upon the mode used.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infrared (FTIR) microspectroscopy has become popular in histopathological and cytopathological research due to its capability to assess biochemical composition and molecular structure of unstained cells and tissues. Several groups have used FTIR microspectroscopy to diagnose skin cancers 1 and other cancers, such as breast, cervical, colorectal, lung, brain, bladder, head and neck cancers. 2,3 These studies have demonstrated the ability of FTIR microspectroscopy to differentiate between diseased and non-diseased conditions.…”
Section: Introductionmentioning
confidence: 99%